دراسة علم الجينات و تطبيقاتها في حياتنا اليومية و علاقتها ببعض الأمراض الوراثية في مجتمعاتنا: باعييس، عمار بيار، حسن - باعييس، عمار بيار، حسن (مجلة الأندلس للعلوم التطبيقية, 2023)
الملخص EN Molecular biology or so-called genetics is a very important modern science in the life of living organisms in general, and in human life in particular, as it is concerned with the study of genes, genetics and subsequent the diversity of organisms. This research discussed the Molecular biology and their basic components such as chromatides, chromosomes and genes. Moreover, it's discussed the uses of microbiology in human daily life and its association with very important areas including those related to agricultural, industrial, environmental and medical sciences. This study also mentioned the symptoms, diagnosis and the treatment methods of Down syndrome, Marfan syndrome, cystic fibrosis and sickle cell disease